Investigation of the Role That NADH Peroxidase Plays in Oxidative Stress Survival in Group B Streptococcus - Korir, Michelle L.; Flaherty, Rebecca A.; Rogers, Lisa M.; Gaddy, Jennifer A.; Aronoff, David M.; Manning, Shannon D. (Frontiers in Microbiology, 2018)
Macrophages play an important role in defending the host against infections by engulfing pathogens and containing them inside the phagosome, which consists of a harsh microbicidal environment. However, many pathogens have developed mechanisms to survive inside macrophages despite this challenge. Group B Streptococcus (GBS), a leading cause of sepsis and meningitis in neonates, is one such pathogen that survives inside macrophages by withstanding phagosomal stress. Although a few key intracellular survival factors have been identified, the mechanisms by which GBS detoxifies the phagosome are poorly defined. Transcriptional analysis during survival inside macrophages revealed strong upregulation of a putative NADH peroxidase (npx) at 1h and 24h post infection. A deletion mutant of npx (Δnpx) was more susceptible to killing by a complex in vitro model of multiple phagosomal biochemical/oxidant stressors or by hydrogen peroxide alone. What is more, compared to an isogenic wild type GBS strain, the Δnpx strain demonstrated impaired survival inside human macrophages and a reduced capacity to blunt macrophage reactive oxygen species (ROS) production. It is therefore likely that Npx plays a role in survival against ROS production in the macrophage. A more thorough understanding of how GBS evades the immune system through survival inside macrophages will aid in development of new therapeutic measures.